2015
DOI: 10.5539/gjhs.v8n6p211
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Cervical Cancer Screening Behaviors Based On the Precaution Adoption Process Model: A Qualitative Study

Abstract: One of the most preventable cancers in women is cervical cancer. Pap smear test is an effective screening program; however, it is not conducted very frequently. The aim of this study is explaining the determinants affecting women’s participation in the Pap smear test based on precaution adoption process model with a qualitative approach. This study was a qualitative approach using a Directed Content Analysis methodology which was conducted in 2014. Participants were 30 rural women who participated in this stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
36
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(49 citation statements)
references
References 24 publications
11
36
0
Order By: Relevance
“…Secondly, our results revealed that many women held inaccurate risk perceptions concerning CC. The women in our sample overestimated the role of heredity; similar to ndings in other studies in Iran (27,36) and other countries (53)(54)(55), which is challenging, since the role of genetic causes of CC is still not clear (56), The vast majority of women reported low perceived risk and susceptibility regarding CC, ndings also reported in other studies (33,34,37,53). We found that women regarded themselves at risk concerning STIs; however, they had poor understanding of the purpose of CCS.…”
Section: Discussionsupporting
confidence: 91%
“…Secondly, our results revealed that many women held inaccurate risk perceptions concerning CC. The women in our sample overestimated the role of heredity; similar to ndings in other studies in Iran (27,36) and other countries (53)(54)(55), which is challenging, since the role of genetic causes of CC is still not clear (56), The vast majority of women reported low perceived risk and susceptibility regarding CC, ndings also reported in other studies (33,34,37,53). We found that women regarded themselves at risk concerning STIs; however, they had poor understanding of the purpose of CCS.…”
Section: Discussionsupporting
confidence: 91%
“…Secondly, our results revealed that many women held inaccurate risk perceptions concerning CC. The women in our sample overestimated the role of heredity; similar to findings in other studies in Iran (27,36) and other countries (52)(53)(54), which is challenging, since the role of genetic causes of CC is still not clear (55), The vast majority of women reported low perceived risk and susceptibility regarding CC, findings also reported in other studies (33,34,37,52). We found that women regarded themselves at risk concerning STIs; however, they had poor understanding of the purpose of CCS.…”
Section: Discussionsupporting
confidence: 91%
“…Differences between STI and cervical cancer management measures and interventions were not clear for women. Other national and international studies also reported a lack of sufficient knowledge about CC, a gap in identifying risk factors and causes of cancer, a lack of recognizing the cervix, and differentiating between STIs and cervical cancer (27,36,51). In addition to comprehensiveness of data and corroborating previous findings regarding women's knowledge of CC and CC testing, the current study sheds light on the importance of establishing explicit knowledge and the role of detailed health education.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…It must be pointed that all subjects entered the study with their willingness. Diagnostic evaluation of females, according to the qualitative study was conducted by the research team, based on precaution adoption process, where all factors affecting the Pap smear-based psychological variables influencing the model using the interview were performed three months after the intervention, again the necessary information from the two groups were collected and analyzed [9].…”
Section: Methodsmentioning
confidence: 99%